External Sustainability of Oil-Producing Sub-Saharan African Countries - York, Robert; Takebe, Misa. (Washington, D.C. : International Monetary Fund, 2011)
In the extensive empirical work carried out across the IMF on oil-producing sub-Saharan African (SSA) countries, the notion of "sustainability" is often directed toward fiscal policies, and, in particular, views on the "optimal" non-oil primary fiscal deficit. The bulk of this work does not, however, address external sustainability, which is a concern especially for those SSA oil producers operating under a fixed exchange rate regime. A couple of recent papers have extended the existing methodologies to assess external sustainability for some oil-producing countries but they do not focus on those in sub-Saharan Africa. In this paper, we bolster this empirical work by providing a range of estimates for the long-run external current external account balance for each of the SSA oil-producing countries, based on three widely used methodologies in the IMF. Our research strategy is to apply these models to the eight countries in the subregion - Angola, Cameroon, Chad, Cote d'Ivoire, Equatorial Guinea, Gabon, Nigeria, and the Republic of Congo - using similar simplifying assumptions so that we are using the same lens to view how they do and do not differ.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet